Influence of Covering Materials and Shading on the Greenhouse Cooling in Iraq - Ali, Issam Mohammed; Albayati, Hind D. R. (Al-Nahrain Journal for Engineering Sciences, 2017)
Cooling greenhouses is essential to provide a suitable environment for plant growth in arid regions. However, using conventional cooling methods are facing many challenges. Filtering out near infra-red radiation (NIR) at the greenhouse cover can significantly reduce the heating load and can solve the overheating problem of the greenhouse air temperature. Four cases of shadings were examined for their ability to improve the indoor condition of a greenhouse cooled by indirect direct evaporative cooler: (shade 1) a single layer of polyethylene film, (shade 2) a double layer of polyethylene film, (shade 3) a double layer of polyethylene film with a green mesh layer (shade 4) a double layer of polyethylene film with a Utrecht Corrugated Cardboard with 3cm holes distributed for incident sun light. An experimental study is conducted to determine the performance parameters of indirect direct evaporative cooling of greenhouse in Baghdad (33.3 oN, 44.4oE) for the four types of shadings. It was found that the percentage reduction in light intensities for shade 1, shade 2 and shade 3 are 15%, 25% and 40% respectively. It percentage reduction solar intensity due to shades is increases at the beginning and ending of sunny period, while it was minimum at noon. The percentage reduction in temperature due to indirect direct evaporative cooling for the shade1, shade 2 and shade 3 and shade 4 are 32.4, 36.3, 42.4, and 47 respectively. The percentage increasing in relative humidity due to indirect direct evaporative cooling for the shade1, shade 2 and shade 3 and shade 4 are 562.5, 729, 871, and 788 respectively. The percentage increasing in temperature due heating load of greenhouse for the shade1, shade 2 and shade 3 and shade 4 are 41.4, 33.2, 20.5, and 11 respectively. The percentage decrease in relative humidity due heating load of greenhouse for the shade1, shade 2 and shade 3 and shade 4 are 43.4, 31, 11.8, and 7 respectively.